2021
DOI: 10.1021/acssuschemeng.1c04389
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Imines by Photo-Oxidative Amine Cross-Condensation Catalyzed by PCN-222(Pd)

Abstract: Palladium-metalated PCN-222 enables the aerobic photo-oxidative cross-condensation of anilines with benzylic amines yielding a series of linear and cyclic imines. The reaction is very efficient under mild conditions, which allows the isolation of simple, yet elusive, intermediates such as 2-(benzylideneamino)­aniline and 2-(benzylideneamino)­phenols. Recyclability studies show excellent activity and selectivity after five runs. The methodology was successfully applied for the synthesis of an antitumor agent (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
(85 reference statements)
0
10
0
Order By: Relevance
“…S1b †). 19,20 On comparing with Fig. S1b, † Pd-Rh@PC (0.25 Pd) still maintains the rod-like structure after carbonization.…”
Section: Characterization Of the Prepared Samplesmentioning
confidence: 76%
“…S1b †). 19,20 On comparing with Fig. S1b, † Pd-Rh@PC (0.25 Pd) still maintains the rod-like structure after carbonization.…”
Section: Characterization Of the Prepared Samplesmentioning
confidence: 76%
“…The FT-IR spectra of PCN-222-M and MTCPP were further obtained to investigate the compositions of the prepared samples . As illustrated in Figure E,F, in comparison with MTCPP, all of the PCN-222-M exhibited an absence of characteristic peaks around 1690 cm –1 (CO bonds) and 1268 cm –1 (C–O bonds), whereas a strong peak appears at 1420 cm –1 (COO symmetric stretch bond), reflecting the coordination of the carboxyl group to the Zr 6 cluster in PCN-222-M and further demonstrating the successful preparation of PCN-222-M .…”
Section: Resultsmentioning
confidence: 99%
“…33,39,40 The FT-IR spectra of PCN-222-M and MTCPP were further obtained to investigate the compositions of the prepared samples. 41 As illustrated in Figure 2E,F, in comparison with MTCPP, all of the PCN-222-M exhibited an absence of characteristic peaks around 1690 cm −1 (C�O bonds) and 1268 cm −1 (C−O bonds), whereas a strong peak appears at 1420 cm −1 (COO symmetric stretch bond), reflecting the coordination of the carboxyl group to the Zr 6 cluster in PCN-222-M and further demonstrating the successful preparation of PCN-222-M. 42 In addition, taking PCN-222-Cu as an example (Figure S1), the characteristic peak of Cu−N slightly shifted to 1004 cm −1 relative to that of CuTCPP (1001 cm −1 ). 43 This further indicated that CuTCPP in PCN-222-Cu possessed reduced intermolecular interactions and quasi-molecular properties, resulting in the exposure of much more active sites for gas adsorption, consistent with the above results of UV−vis spectra and UV−vis DRS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The present copper‐based catalytic system exhibited remarkable activity in oxidative cross‐connection reactions and can be easily recycled (Scheme 1). 20b,23b,29 …”
Section: Introductionmentioning
confidence: 99%